A genetically-encoded chloride and pH sensor for dissociating ion dynamics in the nervous system - Raimondo, Joseph V.; Joyce, Bradley; Kay, Louise; Schlagheck, Theresa; Newey, Sarah E.; Srinivas, Shankar; Akerman, Colin J. (Frontiers in Cellular Neuroscience, 2013)
Within the nervous system, intracellular Cl- and pH regulate fundamental processes including cell proliferation, metabolism, synaptic transmission and network excitability. Cl- and pH are often co-regulated, and network activity results in the movement of both Cl- and H+. Tools to accurately measure these ions are crucial for understanding their role under physiological and pathological conditions. Although genetically-encoded Cl- and pH sensors have been described previously, these either lack ion specificity or are unsuitable for neuronal use. Here we present ClopHensorN - a new genetically-encoded ratiometric Cl- and pH sensor that is optimized for the nervous system. We demonstrate the ability of ClopHensorN to dissociate and simultaneously quantify Cl- and H+ concentrations under a variety of conditions. In addition, we establish the sensor’s utility by characterizing activity-dependent ion dynamics in hippocampal neurons.